2022
DOI: 10.3390/plants11151951
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Apiaceous Potyvirus Phylogeny, Novel Viruses, and New Country and Host Records from Sequencing Apiaceae Samples

Abstract: The family Apiaceae comprises approximately 3700 species of herbaceous plants, including important crops, aromatic herbs and field weeds. Here we report a study of 10 preserved historical or recent virus samples of apiaceous plants collected in the United Kingdom (UK) import interceptions from the Mediterranean region (Egypt, Israel and Cyprus) or during surveys of Australian apiaceous crops. Seven complete new genomic sequences and one partial sequence, of the apiaceous potyviruses apium virus Y (ApVY), carro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The genomes of 14 out of 16 viruses with all RNA segments annotated had three segments, and two monocot-associated ophioviruses had four segments ( Table 1 , Figure 1 ). Three out five of those ophioviruses whose complete genome were assembled, had four RNA segments, which is also a genomic organization of the ophiovirus Mirafiori lettuce big-vein virus (MLBVV) and lettuce ring necrosis virus (LRNV) (Garcia et al, 2017) and the recently reported carrot ophiovirus 1 (Fox et al, 2022). Thus, the most frequent genomic organization found for ophioviruses consists of three RNA segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes of 14 out of 16 viruses with all RNA segments annotated had three segments, and two monocot-associated ophioviruses had four segments ( Table 1 , Figure 1 ). Three out five of those ophioviruses whose complete genome were assembled, had four RNA segments, which is also a genomic organization of the ophiovirus Mirafiori lettuce big-vein virus (MLBVV) and lettuce ring necrosis virus (LRNV) (Garcia et al, 2017) and the recently reported carrot ophiovirus 1 (Fox et al, 2022). Thus, the most frequent genomic organization found for ophioviruses consists of three RNA segments.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, to our knowledge, the diversity of ophioviruses appears to be stagnated, with no new ophiovirus species recognized by the ICTV since 2015. Two recent works have described the complete genome of a novel proposed ophiovirus associated to carrot, carrot ophiovirus 1 (CaOV1) (Fox et al, 2022) and other found in pepper, pepper chlorosis-associated virus (PCaV) (Shimomoto et al, 2023). In addition, the segment that encodes the capsid protein (CP) of a putative novel ophiovirus was assembled from transcriptomic data of Dactylorhiza hatagirea (Sidharthan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Apiaceae species are annual or perennial herbs that are widely distributed in temperate regions of the world (Fox et al, 2022). Recently, the genomes of seven species from Apiaceae, including Apioideae and Mackinlayoideae, have been sequenced (https://www.…”
Section: Introductionmentioning
confidence: 99%
“…plabipd.de/plant_genomes_pa.ep). Apiaceae species have always played an important role in socio-economic and human life, among which Angelica sinensis, Bupleurum chinense, Centella asiatica and O. javanica are medicinal plants (Lu and Li, 2019;Sun et al, 2020;Liu et al, 2022), as well as Apium graveolens, Coriandrum sativum and D. carota are vegetables (Fox et al, 2022). Previous studies have shown that the Ks peak of the paralogous genes in five Apioideae species, including Daucus carota, Oenanthe javanica, A. sinensis, C. sativum and A. graveolens, corresponded to a recent WGD (whole genome duplication) event, possibly specific in Apioideae instead of Mackinlayoideae (Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation